2014
DOI: 10.1371/journal.pone.0086076
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characteristics of Shiga Toxin 2f-Producing Escherichia coli among Pigeons in Kyushu, Japan

Abstract: An increasing number of Shiga toxin 2f-producing Escherichia coli (STEC2f) infections in humans are being reported in Europe, and pigeons have been suggested as a reservoir for the pathogen. In Japan, there is very little information regarding carriage of STEC2f by pigeons, prompting the need for further investigation. We collected 549 samples of pigeon droppings from 14 locations in Kyushu, Japan, to isolate STEC2f and to investigate characteristics of the isolates. Shiga toxin stx 2f gene fragments were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…VT2f-producing E. coli strains isolated from uncomplicated human cases of diarrhea have been reported in the literature as being ST20 ( 11 ), which is the same sequence type we identified in most pigeon isolates; this ST was also described in VT2f-producing E. coli isolated from pigeons in Japan ( 40 ). The same study also described an animal isolate of ST722, which was found in 1 strain isolated from human diarrheal feces in our study (Table 2).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…VT2f-producing E. coli strains isolated from uncomplicated human cases of diarrhea have been reported in the literature as being ST20 ( 11 ), which is the same sequence type we identified in most pigeon isolates; this ST was also described in VT2f-producing E. coli isolated from pigeons in Japan ( 40 ). The same study also described an animal isolate of ST722, which was found in 1 strain isolated from human diarrheal feces in our study (Table 2).…”
Section: Discussionsupporting
confidence: 66%
“…All VT2f strains from HUS that we examined were positive for pathogenicity island OI-122 ( 28 ) and the large virulence plasmid first described in VTEC O157 (Table 2) ( 39 ); the strains from pigeons or from humans with uncomplicated diarrhea did not have these virulence-associated mobile genetic elements (Table 2) ( 10 12 , 32 , 40 ). …”
Section: Discussionmentioning
confidence: 99%
“…Most STEC outbreaks and sporadic cases have been attributed to O157:H7, O26:H11, O111:H8, O45:H2, O103:H2, O145:H28, and O121:H19 (or the nonmotile isolates) (14,(19)(20)(21)(22)(23)(24)(25). Additionally, other STEC serotypes, such as O6:H10, O91:H10/H14/H21, O103: H11/H25, O111:H11/H21, O145:H25/H34, O165:H25, and O178:H19, from foods, animals, and humans, have also been reported (14,22,(24)(25)(26)(27)(28)(29)(30)(31). Two multiplex PCR kits developed in this study, MP-A and MP-B, are particularly useful for distinguishing these H types.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated the prevalence of STEC among urban exploiter species such as rats (Himsworth et al, ) or pigeons (Gargiulo et al, ; Kobayashi, Pohjanvirta, & Pelkonen, ; Murakami et al, ; Silva, Nicoli, Nascimento, & Diniz, ). Likewise, other wild animal species have been investigated such as deer (Asakura et al, ; Carrillo‐Del Valle et al, ; Dunn, Keen, Moreland, & Alex, ) and gulls (Makino et al, ).…”
Section: Introductionmentioning
confidence: 99%